Norwegian (Crusted) Scabies Involving Eyelids and Conjunctiva - Iva Rani Kalita; Harsh Vardhan Singh (Wolters Kluwer Medknow Publications, 2021)
Scabies is a parasitosis caused by the mite sarcoptes scabiei var. hominis, with crusted scabies being more contagious than classic scabies because of a larger mite burden. It can lead to an epidemic of classic scabies if not diagnosed early and treated accordingly. We report a 10-year-old boy who presented with a complaint of an inability to open his left eye and irritation in the right eye. Examination showed the presence of multiple crusted lesions throughout the body, including face and eyelids, and a yellowish patch in the right bulbar conjunctiva. The histopathological evaluation of the specimen of the conjunctival lesion confirmed it to be sarcoptes infestation. Face and eyelids involvement are very rarely in crusted scabies and only a few cases have been reported in the past. Our report demonstrates conjunctiva as an unusual site of involvement in these cases.